Konsep dakwah dalam memperkuat kesatuan umat di era digital - Parwanto, Parwanto; Putra, Rizky Pratama (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
In the context of Muslim life today, da'wah has a very important role in strengthening the unity of the ummah, especially in this digital era. But many of the preachers are wrong in determining the right concept for preaching in this digital era. So this research seeks to present the right concept for preaching that can unite people, especially in this digital era. This research uses a qualitative approach by presenting data sources that are relevant to the discussion by documenting the data obtained, so that it becomes data that is ready to be processed . The results of the analysis of several sources that have been presented, found that the concept of da'wah that is appropriate to unite people in this digital era is divided into three concepts. The first is the concept of da'wah with wisdom or wisdom, then the second is the concept of da'wah with good advice and the third concept is arguing with good arguments.